A single-step, electrochemical synthesis of nitrogen doped blue luminescent phosphorene quantum dots. Issue 83 (2nd October 2018) - Ozhukil Valappil, Manila; Ahlawat, Monika; Pillai, Vijayamohanan K.; Alwarappan, Subbiah
Abstract : A one-step electrochemical preparation of nitrogen doped, blue luminescent phosphorene quantum dots from black phosphorus using a nitrogen-laden solvent and supporting electrolyte. Abstract : Herein, we report a one-step strategy for the electrochemical synthesis of nitrogen doped blue luminescent phosphorene quantum dots (NPQDs) from black phosphorus at room temperature. Nitrogen percentage in NPQDs can be varied by the appropriate choice of solvent and supporting electrolyte. NPQDs [average size 6 ± 1.5 nm ( N = 50)] obtained in this work exhibit ca. 88.7% quantum efficiency.